O conteúdo ético das sentenças - Trevisani, Renato César (2015)
Analysis on the content of the sentences and judicial decisions along with the use of elements based on Natural Law, Philosophy, Moral and on Positive Law, aiming to reduce the technical discussions and to broaden the most philosophical ones, to know that in a society as of so changed values it is up to the Judges the noble function to say what is fair and what is right, because the Judge when sentencing shows part of his moral background. Clarify the importance and the highlight that ethics, ahead of other values, has succeeded which should turn out in the need for studies and more frequent debates among the Judges, considering that the sentence represents what the Judging person felt. That the Ethics is able to revive the belief in institutions and the hope in the future of any nation, as for the social condition which judiciary holds, all of its members are legitimately authorized and called for this need